Factors of illness in primary care health workers (Research, Society and Development, 2022)
Objective: To analyze the factors of illness in health workers in primary care. Methodology: Integrative review, LILACS, PubMed and CAPES databases were used, time frame between 2011 and 2021 with full texts portraying the subject in question, articles in Portuguese, English or Spanish. Of the 76 articles found after observing the inclusion and exclusion criteria, nine publications were selected. Results: Most of the articles analyzed are national, three thematic axes were identified: Risks at work, Precariousness at work and Factors of Illness. Conclusion: The occupational hazards that contribute to illness are physical, biological and chemical, in addition to those caused by the accelerated pressure of time and the increasing demand for productivity caused innumerable harm to the health of the worker. Therefore, it is of fundamental importance to analyze and understand the process of illness at work. In this way, it will be possible to act in a preventive manner in an organizational, collective and individual manner; in micro and macro spaces in work environments, whether in the construction of legislation and public policies in the context of workers' health, proposing interventions that can contribute to the improvement of occupational health conditions.